“It doesn’t feel like exercise”: a realist process evaluation of factors that support long-term attendance at dance classes designed for healthy ageing - Haynes, Abby; Tiedemann, Anne; Hewton, Gail; Chenery, Julie; Sherrington, Catherine; Merom, Dafna; Gilchrist, Heidi (Frontiers in Public Health, 2023)
Introduction Dance can positively impact older people’s health and wellbeing across cultures and socioeconomic groups, countering age-related physical, sensorimotor and cognitive decline. Background/objectives The RIPE (Really Is Possible for Everyone) Dance program aims to improve older people’s physical, mental, cognitive and social wellbeing by integrating engaging dance sequences with evidence-based fall prevention exercises. We sought to identify what mechanisms support observed long-term participation in this program, including by people living with challenging health conditions. Methods Following a realist evaluation approach, we co-developed and tested program theories iteratively with participant interviewees (n = 20), dance teachers (n = 2) and via observation of a dance class. Initial data were dual-coded and emergent findings were interrogated by the research team. Findings were organised to express Program activities + Context + Mechanism = Process outcomes configurations. Results We identified four program theories comprising 14 mechanisms which explained long-term attendance: 1. RIPE Dance benefits my body and mind (trust in the program, belief in health benefits), 2. RIPE Dance helps me feel good about myself (self-efficacy, pride in achievement, psychological safety, defying expectations, feeling valued), 3. RIPE Dance creates camaraderie (social connection, mutual support, rapport with the teacher), and 4. RIPE Dance is uplifting (raised spirits, fun, synchrony, musical reactivity). Conclusion The RIPE Dance program provides effective and enjoyable ‘exercise in disguise’ for older people with diverse mobility profiles. Significance/implications This research confirms that participation in dance can contribute significantly to healthy, happy ageing. Findings detail program activities that were most strongly associated with process outcomes, offering guidance for further program development, implementation and scaling up.